Media Pembelajaran E-Learning Pendidikan Anak Usia Dini Berbasis Website - Christian, Efrans; Ehuwinae, Okta (Universitas Palangka Raya, 2021)
Pendidikan Anak Usia Dini (PAUD) plays a major role in supporting the physical and spiritual development of early childhood before entering elementary school. Therefore, a Website-Based Learning Media Application for Pendidikan Anak Usia Dini (PAUD) was made, so that children can learn anywhere and anytime. The methodology used in making the Design of Learning Media Applications for Website-Based Pendidikan Anak Usia Dini (PAUD) was made using the waterfall software development methodology according to Summerville in 2011, which has stages, namely requirements definition, drawn using flowcharts, requirements analysis and definition drawn through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and database. Implementation and unit testing with the programming languages ​​used, namely HTML, PHP, CSS, Boostrap, Javascript and Mysql. Integration and system testing using the blackbox method. On this website there are several features, namely homepage, materials, about and contact us. With the aim that early childhood and parents more easily and quickly get information.